DESCRIPTION AND PRICING OF SELECTED TWO-ASSET OPTIONS AND SUGGESTIONS CONCERNING THEIR USE ON THE GRAIN MARKET IN POLAND - Krawiec, Monika (Acta Scientiarum Polonorum. Oeconomia, 2013)
Multi-asset options are options with payoffs affected by at least two underlying instruments. These instruments can be assets such as stocks, indices, currencies or commodities. An important factor influencing values of multi-asset options is correlation among log-returns of underlying assets. Thus the options are also called correlation options. In the paper there are presented description and models for pricing selected correlation options: quotient, product, spread and two-color rainbow options. There are also given some examples of their use on the grain market in Poland.